CONVENTIONAL LINEAR TOMOGRAPHY IMAGING FOR MANDIBULAR IMPLANTS TREATMENT - Diah Indriastuti; Menik Priaminiarti (Faculty of Dentistry, Universitas Indonesia, 2015)
Radiographic examination has a very important role in dental implant treatment, including preoperative planning and intraoperative and postoperative assessment. In preoperative planning, radiographic examination has an ability to visualize critical anatomic organs such as mandibular formaen, mandibular canals, and mental foramen, which will guide the choice of implant length, diameter, and position. Besides, it also can reveal variation of quality of the jawbone. Radiographic examination for postoperative assessment of dental implant is usually addressed for evaluation of implant position. Development and application modern imaging modalities in dento-maxillofacial radiology have very important role for better accuracy and more comprehensive dental implant treatment. One of modern radiographic imaging techniques for this purpose is conventional linear tomography. This modality yields visualization of bone quality and quantity in high detail and accuracy, including bone condition in buccal-lingual dimension. Thus the choice of implant type, shape, and size can be obtained precisely and furthermore reducing iatrogenic damage of critical anatomic organ Radiation dose of conventional linear tomography is relatively low compared with other modern imaging modalities such as CT scan, besides that it also has lower cost so it has beneficial economic point. However, for a certain case and condition, there will be more need for combining conventional linear tomography with other techniques, such as the panoramic and periapical technique.